(untitled) (Bulletin KNOB, 1999)
In the autumn of 1566, soon after the fierce iconoclasm troubles, the Protestant urban communities erected several temples in the Low Countries. After one year only, these temples were destroyed as a result of the order given by the regent Margaret of Parma. Archival sources and tangible material are very rare and have survived for only a few of these. Three temples in Antwerp had an elliptically shaped ground plan and had been constructed of wood on a stone basement. The temple at Gent, known from a description and a sketch by Van Vaernewijck, was octagonal in shape and made with wooden posts and bricks with a straw roof. Here, a ‘classically’ designed pulpit was placed in the center. Men and women were seated separately. Temples were also erected in Oudenaarde, Haarlem, Gorcum and Leiden. However, no additional information has been found in these cases. The choice of materials and finishing used in the temple construction suggests continuation of an age-old shed building practice. The preference for a centrally planned design is likely to have been prompted by a liturgical need to bring together as many people as possible within hearing distance of the preacher. However, one cannot exclude an influence of Renaissance treatises, such as the Flemish translation of the fifth book of Serlio published by Mayken Verhulst, the wife of Pieter Coecke van Aelst, at Antwerp in 1553. The appearances as well as the functional organisation of the temples are related to contemporary and later French examples such as ’Le Paradis’ at Lyon (1563) or the temples of Dieppe (1600) and Caen (1611). Protestant communities had close connections with each other on an international level and concepts about temple building were undoubtedly widely held. Although an influence of the Temple of Salomon, traditionally presented as round shaped, is often suggested, contemporary descriptions do not confirm this view. Only in later texts this connection is made, possibly inspired by the early 17th-century Protestant building and legitimisation practice, where the topic of the Temple of Salomon is used very often.